2019
DOI: 10.1002/mgg3.1030
|View full text |Cite
|
Sign up to set email alerts
|

Potentially functional variants of autophagy‐related genes are associated with the efficacy and toxicity of radiotherapy in patients with nasopharyngeal carcinoma

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is one of the major invasive malignant neoplasms of head and neck, while radiotherapy is the primary therapy for NPC. Genetic variants could affect the efficacy and toxicities of radiotherapy in NPC patients.MethodsIn the current study, we aimed to investigate 10 potentially functional SNPs of autophagy‐related genes (ATG) with the efficacy and toxicity of radiotherapy in 468 NPC patients.ResultsWe found ATG10 rs10514231, rs1864183, and rs4703533 were significantly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…In this regard, autophagy-related polymorphisms are not only involved in the development of pathologies, but also may influence the effectiveness of a determined treatment. This additional clinical relevance of variants on autophagy-related genes has already been described in cancer [ 61 , 104 , 114 , 118 , 121 ], inflammatory bowel diseases [ 145 , 346 , 347 ] and others [ 80 ]. For this reason, the identification of new clinically significant SNPs is not only important in terms of disease prevention, but also to design new therapeutic approaches aimed at modulating autophagy for clinically relevant purposes.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this regard, autophagy-related polymorphisms are not only involved in the development of pathologies, but also may influence the effectiveness of a determined treatment. This additional clinical relevance of variants on autophagy-related genes has already been described in cancer [ 61 , 104 , 114 , 118 , 121 ], inflammatory bowel diseases [ 145 , 346 , 347 ] and others [ 80 ]. For this reason, the identification of new clinically significant SNPs is not only important in terms of disease prevention, but also to design new therapeutic approaches aimed at modulating autophagy for clinically relevant purposes.…”
Section: Discussionmentioning
confidence: 70%
“…In fact, variants affecting different genes from this system are associated with the same pathology. For example, pathogenic alleles of ATG5 , ATG10 , ATG12 and ATG16L1 have been all linked to changes in susceptibility or treatment efficiency in neck squamous cell cancer [ 103 , 114 , 115 , 116 ], hepatocellular carcinoma [ 117 ] and lung adenocarcinoma [ 118 ] and others have been found to also affect development of other types of cancer, such as melanoma [ 119 ], brain metastases in patients with non-small lung cancer [ 120 ] or breast cancer [ 121 , 122 , 123 , 124 ]. Moreover, there is also an association between SNPs in ATG5 and ATG7 with clear cell renal cell carcinoma [ 125 ] and variants of ATG5 and ATG10 have been linked to non-small cell lung cancer [ 126 , 127 ].…”
Section: Relevant Variants On Autophagy-related Genesmentioning
confidence: 99%
“…We evaluated 22 cancer risk SNPs in autophagy-related genes for their gene regulatory activity with the DiR system and discovered multiple functional SNP sites, among which rs10514231 showed significant activity in most breast cancer cells we used. This SNP was located in the second intron of the ATG10 gene and had been reported to have a significant association with susceptibility for breast cancer and many other diseases in Chinese populations [21]. Analysis using the online tool HaploRegv4.1 revealed that rs10514231 was located in the enhancer histone modification marks in more than ten types of cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…The rs10514231 is located in the second intron of ATG10 and has been reported for association with breast cancer risk (C allele: OR = 0.75, 95%CI: 0.59-0.93, p = 0.010) [20]. Besides, it also exhibited a significant association with a predisposition for lung cancer, hepatocellular carcinoma, and nasopharyngeal carcinoma [21][22][23]. Nevertheless, the pathogenesis mechanism was poorly investigated.…”
Section: Rs10514231 Shows Enhancer Activity In Breast Cancer Cellsmentioning
confidence: 99%
“…The ATG family tends to regulate the production of autophagic vesicles [22], while ATG10, a member of the ATG family, is also closely associated with tumorigenesis and development, e.g., high expression of ATG10 in colorectal cancer is associated with lymphovascular in ltration and lymph node metastasis, leading to tumor migration and invasion [23]. In addition, overexpression of ATG10 in cancers such as nasopharyngeal, hepatocellular, and gastric cancers has been associated with poor patient prognosis [24][25][26]. Past studies have found that overexpression of SIRT1 is associated with ES metastasis and poor prognosis, while the SIRT1 / 2 inhibitor Tenovin-6 kills ES cells in vitro [27].…”
Section: Discussionmentioning
confidence: 99%